Empowering Rural Youth Groups through Islamic Social Enterprise (ISE) in Indonesia - Hati, Getar (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
Indonesia has a bonus demography challenge. For this reason, youth development should be prioritized by considering the unproductive migration of rural youth groups. Islamic social enterprise (ISE) offers a strategic approach to empowering the youth. This study investigated youth empowerment through vocational training programs provided by two ISE organizations. This is a descriptive qualitative study. Online interviews were carried out from October 2021 to June 2022 involving eight ISE program participants. The research finding shows that ISE supported intellectual, psychological, spiritual, and social skill development. The results also suggest comprehensive support from the government, private sectors, and local communities to ensure the youth groups can be change agents for their villages. Keywords: change agent, community development, social enterprise, youth empowerment Abstrak Indonesia menghadapi tantangan bonus demografi. Untuk itu, pembangunan untuk kelompok harus diprioritaskan dengan mempertimbangkan adanya masalah migrasi yang tidak produktif oleh kelompok pemuda dari wilayah perdesaan. Kewirausahaan sosial berbasis nilai Islam menawarkan pendekatan strategis untuk memberdayakan kelompok pemuda. Studi ini mendeskripsikan pemberdayaan pemuda melalui program pelatihan vokasi yang dilakukan oleh dua organisasi. Studi ini menggunakan pendekatan kualiatif deskriptif. Wawancara online dilakukan sejak Oktober 2021 hingga Juni 2022 dengan melibatkan delapan peserta program. Hasil penelitian menunjukkan bahwa Kewirausahaan sosial berbasis nilai Islam mendukung perkembangan intelektual, perkembangan psikologis dan spiritual, serta perkembangan keterampilan sosial. Hasil penelitian merekomendasikan dukungan komprehensif dari pemerintah, sektor swasta, dan masyarakat lokal untuk dapat memastikan keberdayaan kelompok pemuda sebagai agen perubahan bagi desa mereka. Kata kunci agen perubah, pengembangan komunitas, kewirausahaan sosial, pemberdayaan pemuda